Analisis Strategi Peningkatan Kinerja Perusahaan dengan Pendekatan Matriks SWOT dan Matriks Space Pada PT.XYZ - Muhamad Khusnul Khuluq; Nur Rahmawati (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
In measuring company performance, several aspects are needed to identify and evaluate company performance. With increasingly tight competition in the business world, many companies are utilizing various business strategies as support to improve their performance. Implementing a business strategy will be beneficial if its implementation is in accordance with the company's goals, vision and mission. Implementation of business strategy aims to support the company's growth and long-term targets. PT. XYZ is one of the companies in the maritime sector that is currently experiencing quite good business growth, in an effort to achieve its goals. One method of analyzing company strategy is to use the SWOT matrix (Strength, Weakness, Opportunity and Threat) and the SPACE Matrix, namely analyzing from an internal company perspective by reviewing the strengths and weaknesses that exist within the company and from an external company perspective by reviewing the company's internal aspects. opportunities and threats that exist outside the company which are then created a matrix to determine PT's position. XYZ. Based on the IFAS matrix, PT XYZ' position is in a relatively good position in facing its internal environment with a value of 2.80. Meanwhile, PT XYZ' EFAS position matrix is in a relatively good position in facing its external environment with a total value of 3.10. From the results of research on strategies to improve company performance at PT. XYZ was found to be in an Aggressive position..